FM 2011: Formal Methods 17th International Symposium on Formal Methods, Limerick, Ireland, June 20-24, 2011. Proceedings - Butler, Michael; Schulte, Wolfram; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 17th International Symposium on Formal Methods, FM 2011, held in Limerick, Ireland, in June 2011. The 29 revised full papers presented together with 3 invited talks were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on cyber-physical systems, runtime analysis, case studies/tools, experience, program compilation and transformation, security, progress algebra, education, concurrency, dynamic structures, and model checking.
Keywords: Computer science; Software engineering; Logic design; Information Systems; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Programming Techniques; Mathematical Logic and Formal Languages; Management of Computing and Information Systems